2020
DOI: 10.1111/jcmm.15005
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal M2 macrophage transplantation as a potential cell therapy for enhancing renal repair in acute kidney injury

Abstract: Acute kidney injury (AKI) is a clinical condition that is associated with high morbidity and mortality. Inflammation is reported to play a key role in AKI. Although the M2 macrophages exhibit antimicrobial and anti‐inflammatory activities, their therapeutic potential has not been evaluated for AKI. This study aimed to investigate the protective effect of peritoneal M2 macrophage transplantation on AKI in mice. The macrophages were isolated from peritoneal dialysates of mice. The macrophages were induced to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
2
44
0
Order By: Relevance
“…These studies highlight the complexity and importance of these cells in response to infection and inflammation (55,57), but also reveal their role in immune homeostasis (1,2,58,59). Peritoneal macrophages follow similar activation pathways to other macrophage lineages, where M1 macrophages activated by IFNg and TNFa have enhanced microbicidal or tumoricidal capacity and secrete high levels of pro-inflammatory cytokines and mediators (60), while IL-4 activated M2 macrophages reduce inflammation and contribute to tissue repair through secretion of IL-10 and TGF-b (61,62). Although M2 macrophages have antiinflammatory roles, dysregulation of these signaling pathways also induce inflammation and immunopathology (38), which we investigated using the in vivo model of IL-4c induced peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlight the complexity and importance of these cells in response to infection and inflammation (55,57), but also reveal their role in immune homeostasis (1,2,58,59). Peritoneal macrophages follow similar activation pathways to other macrophage lineages, where M1 macrophages activated by IFNg and TNFa have enhanced microbicidal or tumoricidal capacity and secrete high levels of pro-inflammatory cytokines and mediators (60), while IL-4 activated M2 macrophages reduce inflammation and contribute to tissue repair through secretion of IL-10 and TGF-b (61,62). Although M2 macrophages have antiinflammatory roles, dysregulation of these signaling pathways also induce inflammation and immunopathology (38), which we investigated using the in vivo model of IL-4c induced peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are highly plastic cells, which can respond to subtle changes in the tissue microenvironment by initiating several activation programs. The activation of macrophages occurs according to two main types of program: the classic inflammatory activation (M1), of which the activating stimuli are bacterial molecules (e.g., LPS) and inflammatory cytokines, and the alternative activation (or M 2 ) , s t i m u l i a c t i v a t o r s o f w h i c h a r e t h e a n t iinflammatory cytokines (e.g., IL-4), immune complexes or glucocorticoids [32,63]. The initial inflammatory response activates the M1 polarization of macrophages, which become able to eliminate the invading new microorganisms, and promote the inflammatory response, while during the inflammation resolution phase, in which the increase of IL-4 plays a determining role, the macrophages are repolarized in the M2 direction, losing their reactivity to inflammatory stimuli, and assuming the ability to eliminate damaged cells and tissues, and to promote angiogenesis and tissue repair [64].…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is considered that M2 macrophages and regulatory T cells are critical cells controlling inflammation, as well as tissue remodeling and repair following AKI (30). Previous studies have shown that M2 macrophage therapy can effectively reduce renal injury in AKI mice (31,32). The increase in M2 macrophages may play a pivotal role in the initial damage of human AKI and in the transition from AKI to chronic kidney disease (CKD) (33).…”
Section: Major Signaling Pathways and Key Mediators Of Macrophages In Acute Kidney Injury (Review)mentioning
confidence: 99%